Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1590/1806-9282.61.02.178
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in women with urinary incontinence

Abstract: Conflict of interest: noneThe aim of this study is to examine the relationship among psychological, clinical and sociodemographic variables, and quality of life in women with urinary incontinence. The sample consisted of 80 women diagnosed with urinary incontinence (UI) followed in a Northern Central Hospital in Portugal. Participants answered the Incontinence Quality of Life (I-QOL); Satisfaction with Sexual Relationship Questionnaire (SSRQ); Hospital Anxiety and Depression Scales (HADS) and the Brief Cope. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
4
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 50 publications
(51 reference statements)
8
47
4
6
Order By: Relevance
“…This supported with the study carried out among four developed countries who found The present study showed a statistically signifi cant differences between Yemeni and Egyptian women as regards symptoms of anxiety and depression (p=0.003).The largest percent of psychological symptoms among Yemeni women were in anxiety and depression, while in Egyptian women were somatization and phobic anxiety. This result in agreement with Senra et al [22] who reported that more than one third of women with UI had depressive and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…This supported with the study carried out among four developed countries who found The present study showed a statistically signifi cant differences between Yemeni and Egyptian women as regards symptoms of anxiety and depression (p=0.003).The largest percent of psychological symptoms among Yemeni women were in anxiety and depression, while in Egyptian women were somatization and phobic anxiety. This result in agreement with Senra et al [22] who reported that more than one third of women with UI had depressive and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…An Arab study found that women with MUI lost urine more times, in greater quantity and with greater impact on daily life, reaching the worst scores of the questionnaire compared to women with other UI subtypes (25) . However, some studies highlight the severity of symptoms (amount of urine loss and frequency of loss), rather than the UI subtype as the most important predictive factor for a poorer QoL (26)(27) .…”
Section: Discussionmentioning
confidence: 99%
“…UI considerably reduces the QoL of women and it leads to depression [7] . However, most of the patients do not regard their symptoms as abnormal or serious and some of them do not consult a doctor because of shyness [3] .…”
Section: Introductionmentioning
confidence: 99%